Maple syrup urine disease: Clinical outcomes, metabolic control, and genotypes in a screened population after four decades of newborn bloodspot screening in the Republic of Ireland. Issue 3 (20th December 2020) - O'Reilly, Daniel; Crushell, Ellen; Hughes, Joanne; Ryan, Stephanie; Rogers, Yvonne; Borovickova, Ingrid; Mayne, Philip; Riordan, Michael; Awan, Atif; Carson, Kevin; Hunter, Kim; Lynch, Bryan; et al.
Abstract: Since 1972, 18 patients (10 females/8 males) have been detected by newborn bloodspot screening (NBS) with neonatal‐onset maple syrup urine disease (MSUD) in Ireland. Patients were stratified into three clusters according to clinical outcome at the time of data collection, including developmental, clinical, and IQ data. A fourth cluster comprised of two early childhood deaths; a third patient died as an adult. We present neuroimaging and electroencephalography together with clinical and biochemical data. Incidence of MSUD (1972‐2018) was 1 in 147 975. Overall good clinical outcomes were achieved with 15/18 patients alive and with essentially normal functioning (with only the lowest performing cluster lying beyond a single SD on their full scale intelligence quotient). Molecular genetic analysis revealed genotypes hitherto not reported, including a possible digenic inheritance state for the BCKDHA and DBT genes in one family. Treatment has been based on early implementation of emergency treatment, diet, close monitoring, and even dialysis in the setting of acute metabolic decompensation. A plasma leucine ≥400 μmol/L (outside therapeutic range) was more frequently observed in infancy or during adolescence, possibly due to infections, hormonal changes, or noncompliance. Children require careful management during metabolic decompensations in early childhood, and this represented a key risk period in our cohort. A high level of metabolic control can be achieved through diet with early implementation of a "sick day" regime and, in some cases, dialysis as a rescue therapy. The Irish cohort, despite largely classical phenotypes, achieved good outcomes in the NBS era, underlining the importance of early diagnosis and skilled multidisciplinary team management. Abstract :